Quantifying late Quaternary Australian rainfall seasonality changes using the Poaceae:Asteraceae pollen ratio. (July 2021) - Herbert, Annika V.; Fitchett, Jennifer M.
Abstract: Mounting evidence suggests that the Southern Westerly Winds were significantly equatorially displaced and more intense during the last glacial maximum (LGM), prompting deliberate research identifying proxies to reconstruct these changes. This has focused on rainfall seasonality to track changes in major circulation patterns across the southern hemisphere midlatitude regions. Using a common methodology to reconstruct climatic changes aids comparability and makes it easier to draw significant conclusions regarding general circulation movements. We assess the applicability of Coetzee's (1967) Poaceae:Asteraceae pollen ratio, which has been used successfully in South Africa, in the Australian context. The ratio scores from modern samples fail to capture the weak seasonality in the southeast and on Tasmania but is successful for the rest of the continent. The periods of greatest change compared to present day match known periods of distinct climatic events, namely the mid-Holocene (6–7 cal ka BP), the last deglacial period (15–17 cal ka BP), and two periods during the LGM (20–22 and 31–33 cal ka BP), suggesting large parts of Australia experienced a "double peak" of rainfall seasonality change during the LGM. This confirms that the Poaceae:Asteraceae pollen ratio can be used on records outside of South Africa.